An Analysis of Student's Javanese Language Interference in Pronunciation of English - Miftahur Rahmah; Ainur Rohmah; Hastuti Retno Kuspiyah (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2023)
AbstractIn this study concern with an analysis students’ Javanese language interference in pronunciation English at the fourth semester students of English education program of Nurul Huda University. The study aim to identify the forms of phonological interference in the Javanese dialect in the school, along with its causal factors. This study was a qualitative descriptive study with a sociolinguistic approach.The technique for collecting the data were test consisted some word from oxford dictionary to pronoun especially in word have (/d/) in reading passage and student read by Javanese dialect, recording and observation. The technique for collecting the data were test consisted of 20 words from the text and 20 respondent Javanese people, the technique for analyzing the data are data reduction, data display and conclusion drawing/verification. The writer found that the Javanese learners of English encountered difficulties in pronouncing especially in the accent the sound /d/ in final position in voiceless /t/, Based on the findings, the writer found that students’Javanese pronunciation interference of the fourth semester students of English education program of Nurul Huda University was pronuncing accent in final position /d/ with the result test of pronunciation was 329 words from 20 respondents and for the result of observation was 11 words not interference and interference of pronunciation test was 73 words with 20 respondents.Keywords : Javanese, Interference, Pronunciation